Chemical constituent, antibacterial and antioxidant activity of crude extract and oil fraction of L. abyssinica - Fodouop Chegaing Pierre; Donatien Gatsing; Gerald Ngo Teke; Xavier Cheseto; Benjamin Talom Tangue; Jules-Roger Kuiate; Baldwin Torto (International Journal of Phytomedicine, 2014)
The antibacterial and antioxidant activities of CH3Cl/MeOH crude extract and a nonpolar fraction from the CHCl3 phase of Ludwigia abyssinica were investigated using broth dilution method and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging assay respectively. Chemical composition was determined by gas chromatography coupled with mass spectrometry using Agilent Technologies 7890A GC system-Agilent Technologies 5975C inert XL EI/CI MSD. Bioassays show that L. abyssinica is active on the different test organisms with the MIC ranging from 0.5 to 1.5 mg/ml for the crude extract and 0.2 to 0.5 mg/ml for the non polar oil fraction. The oil extract of L. abyssinica exhibited a good antioxidant activity with radical scavenging activity (IC50) = 89.18 µg/ml which is about 1.5 times the antioxidant activity of ascorbic acid used as control, while that of crude extract was 413.74 µg/ml. From the gas chromatography coupled with mass spectrometry analyses, 12 hydrocarbons were identified with octadecane (5.67%), pentadecane (6.87%) and squalene (57.18%) the major components. These results offer a plat form of using L. abyssinica for alternative and complementary medicine.